2021
DOI: 10.3390/molecules26061626
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pressurized Liquid Extraction of Lycopodiaceae Alkaloids Obtained from Two Lycopodium Species

Abstract: Alkaloids of the Lycopodiaceae family are of great interest to researchers due to their numerous properties and wide applications in medicine. They play a very important role mainly due to their potent antioxidant, antidepressant effects and a reversible ability to inhibit acetylcholinesterase (AChE) enzyme activity. This property is of immense importance due to the growing problem of an increasing number of patients with neurodegenerative diseases in developed countries and a lack of effective and efficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The purified alkaloid samples obtained from all experiments (104 in total) from the three plant species were analyzed using HPLC/ESI-QTOF-MS. This is a reliable tool for the efficient determination of unknown compounds present in plant extracts, as documented in many of our works [23,26]. This technique has numerous advantages such as high sensitivity, high mass accuracy (below 1 ppm) and high reproducibility of the analysis.…”
Section: Lc-ms Identification Of the Isolated Compoundsmentioning
confidence: 92%
See 3 more Smart Citations
“…The purified alkaloid samples obtained from all experiments (104 in total) from the three plant species were analyzed using HPLC/ESI-QTOF-MS. This is a reliable tool for the efficient determination of unknown compounds present in plant extracts, as documented in many of our works [23,26]. This technique has numerous advantages such as high sensitivity, high mass accuracy (below 1 ppm) and high reproducibility of the analysis.…”
Section: Lc-ms Identification Of the Isolated Compoundsmentioning
confidence: 92%
“…Three plant species belonging to the Lycopodiaceae family: L. clavatum, L. annotinum, H. selago, were subjected to extraction using the PLE method. The conditions of this process were previously carefully selected through many trials and studies in our laboratory, and the results were published [26]. Based on these studies, it was found that the highest percentage of Lycopodium alkaloids were isolated under high pressure and temperature (100 bar, 80 • C) from methanolic extracts, so these conditions were used in this approach.…”
Section: Optimization Of Alkaloid Fractionation and Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the Amaryllidaceae alkaloids (such as galanthamine or lycorine) were eluted with 80-100% recovery [22]. The same procedure was used for the extraction and purification of Lycopodiaceae alkaloids [25]. These methods allowed gaining results with high accuracy and ascertaining the influence of types of solvents on the obtained amount of alkaloids.…”
Section: Methods Of Isolationmentioning
confidence: 99%